Pengaruh Motivasi Dan Disiplin Terhadap Kinerja Karyawan Pada PT. Cilpan Finance Tanggerang II - Roni; Fadli, Roni; Mulyani, Sri; Setianingsih, Setianingsih (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
The purpose of this study is to determine the effect of compensation and motivation on turnover intention at PT. Bina Putra Makmur Nusantara. This study uses quantitative methods, with a population size of 51 respondents with saturated sampling type, namely all employees at PT. Bina Putra Makmur Nusantara. Collecting data using a questionnaire distributed to employees of PT. Bina Putra Makmur Nusantara. The collected data was then analyzed using Validity Test, Reliability Test, Classic Assumption Test, Simple Linear Regression Test, Multiple Linear Regression Test, Coefficient of Determination Test and Hypothesis Testing with the help of SPSS Version 25 program. Compensation variables have a negative effect on performance at PT. Bina Putra Makmur Nusantara, based on the results of an analysis of the influence of factors that influence turnover intention, shows tcount < ttable, namely -2.720 < 2.009, sig 0.009 < probability 0.05. Motivation variable has a positive and significant effect on performance at PT. Bina Putra Makmur Nusantara, motivation variable has the most dominant influence on performance with tcount > ttable, which is 4.652 > 2.009, and sig 0.000 < probability 0.005. Compensation and motivation variables together and simultaneously have a positive and significant effect on the performance of PT. Bina Putra Makmur Nusantara, because the fcount is greater than the ftable value, namely 137,048 > 3.19 with a significant level of < 0.05, which is 0.000.